Experimental investigation of graphite explosive-emission cathodes operating in a periodic pulse regime - Korovin S. D.; Litvinov E. A.; Mesyats G. A. Gennady Andreyevich; Murzakaev A. M.; Rostov V. V.; Shpak V. G.; Shunailov S. A.; Yalandin M. I. (2004, 2004)
В фонде НТБ ТПУ отсутствует